Reseña de Hargreaves, A. (2023). Leadership From the Middle: The Beating Heart of Educational Transformation. Taylor & Francis. (Revista Peruana de Investigación Educativa, 2024)
Reseña de libro: Leadership From the Middle. The Beating Heart of Educational Transformation, de: Andy Hargreaves. Publicado en Augosto 2023 por Routledge.